Analisis Spasial Hubungan Sebaran Hotspot, Perubahan Stok Karbon, dan Karakteristik Lahan (Kawasan Hutan dan Ketebalan Gambut) di KHG Kahayan Sebangau, Kalimantan Tengah Tahun 2018-2022: Spatial Analysis of Hotspots, Carbon Stock Changes and Land Properties in Peatland Hydrology Unitary (KHG) Kahayan-Sebangau, Central Kalimantan in 2018 – 2022 - Atmaja, Krisologus Genesa Ruby; Rahman, Basuki; Santosa, Lenalda Febriany; Sholihah, Rizqi I’anatus; Wulandari, Verlina Intan (JURNAL HUTAN TROPIKA, 2025)
Peatland fires have been a long-standing topic of discussion in combating greenhouse gas effects, especially in Indonesia, which has the largest tropical peatlands in the world. However, peatland fires have their own complexities, one of which is that hotspots do not always reflect the amount of carbon emissions. This study was conducted in the Kahayan-Sebangau Peatland Hydrological Unitary (KHG) by integrating several spatial data sets: MODIS hotspot distribution data from 2019 to 2022, peat thickness data, forest area status data, land cover data from 2018 and 2022 with carbon content values based on the 2015 national guidelines of the Ministry of Environment and Forestry (KLHK). Carbon emissions were estimated from changes in land cover and carbon reserves per hectare. The results show that Production Forests (HP) contribute >40% of total hotspots and >80% of carbon emissions, while Conversion Production Forests (HPK) have the highest hotspot density at 1.08 hotspots/km2 and the highest carbon emissions are found in the deep peat thickness class. This study found that the status of forest areas and peat thickness greatly determine the amount of carbon emissions from a fire, as indicated by the distribution of hotspots.